Physical problem in interpreting classical energy of soliton of sine Gordon equation. Issue 1 (April 2021) - Prayitno, T B; Budi, E; Sunaryo, S; Fahdiran, R
Abstract: The classical energy of soliton of sine Gordon equation was evaluated by using the Hamiltonian density. We classify the condition at which the energy will be either convergent or divergent. For the convergent energy, we also impose the condition at which the energy is real. We justify that there is a satisfied condition to obtain real energy.